Exploring the Enablers and Barriers of Developing Remote Cross-cultural Collaboration Between a Rwandan Primary School and a Welsh University - Young, Nick; Chapman, Sammy; Cloke, Sally; Woolridge, Brad; Hodgkin, Kieran; Brooks, Paul (International Journal of Multicultural Education, 2025)
The study identifies key enablers and barriers to effective remote cross-cultural collaboration between Rwandan primary teachers and Welsh academics engaged in collaborative learning. Qualitative analysis of focus group data identified the role of shared interests, consistent communication, and cultural sensitivity in enabling successful collaborations and the potential of technology and logistics to create barriers. The study extends an established framework of first- and second-order barriers to include enabling influences, highlighting the important role of internal factors such as cultural perceptions and personal attitudes in remote cross-cultural collaborations, and providing new insights for educators and policymakers.